2004
DOI: 10.1016/s0002-9440(10)63362-7
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Ataxia, Seizures, Premature Death, and Cardiac Abnormalities in Mice with Targeted Disruption of the Cacna2d2 Gene

Abstract: CACNA2D2 is a putative tumor suppressor gene located in the human chromosome 3p21.3 region that shows frequent allelic imbalances in lung, breast, and other cancers. The ␣2␦-2 protein encoded by the gene is a regulatory subunit of voltage-dependent calcium channels and is expressed in brain, heart, and other tissues. Here we report that mice homozygous for targeted disruption of the Cacna2d2 gene exhibit growth retardation, reduced life span, ataxic gait with apoptosis of cerebellar granule cells followed by P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
80
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 48 publications
11
80
0
1
Order By: Relevance
“…We observed that both Mlc1 ‐null and Glialcam ‐null mice showed hindlimb clasping when suspended from the tail (Fig 2). This is a sign of neurological abnormality, co‐occurring with seizures or increased seizure susceptibility in several mouse models for neurological diseases 30, 31…”
Section: Resultsmentioning
confidence: 99%
“…We observed that both Mlc1 ‐null and Glialcam ‐null mice showed hindlimb clasping when suspended from the tail (Fig 2). This is a sign of neurological abnormality, co‐occurring with seizures or increased seizure susceptibility in several mouse models for neurological diseases 30, 31…”
Section: Resultsmentioning
confidence: 99%
“…The homozygous null mice also had an increased frequency of bradycardia, but also a smaller reduction of heart rate in response to isoflurane anaesthesia, suggesting that the sympathetic regulation of cardiac functions is altered in this mouse model (Ivanov et al, 2004). Similarities between the cacna2d2 null mouse and the cacna1a null mouse (Fletcher et al, 2001) suggested to Ivanov et al (2004) that the same channel (that is, the Ca V 2.1 channel that regulates P/Q-type currents) was involved and in support of this the P-type currents are reduced in the Purkinje cells of ducky homozygotes (Barclay et al, 2001). Interestingly, the drug gabapentin which has analgaesic and antiepileptic uses can bind to a2d1 a2d2, but not a2d3 a2d4.…”
Section: Cacna2d2mentioning
confidence: 93%
“…This mouse strain, named for its ataxic duck like gait was demonstrated to harbour a mutant cacna2d2 allele (Barclay et al, 2001) and is a mouse model for absence epilepsy with spike wave seizures and cerebellar ataxia. A cacna2d2 mouse knockout was generated and extensively characterized (Ivanov et al, 2004); exons 33-39 were replaced with a neomycin resistance cassette; the homozygous null mice were viable, but had an increased frequency of unexplained death, growth retardation, ataxia, increased levels of apoptosis in the granular layer of the cerebellum followed by loss of the cerebellar Purkinje cells, and an increased susceptibility to P2T induced seizures. The homozygous null mice also had an increased frequency of bradycardia, but also a smaller reduction of heart rate in response to isoflurane anaesthesia, suggesting that the sympathetic regulation of cardiac functions is altered in this mouse model (Ivanov et al, 2004).…”
Section: Cacna2d2mentioning
confidence: 99%
See 1 more Smart Citation
“…80 Targeted disruption of the Cacna2d2 gene leads to ataxia and enhanced seizure susceptibility. 81 In sum, a common factor in these six very different mouse syndromes expressing absence-like seizures is impaired function in presynaptic Ca 2ϩ channels (P/Q-type) controlling neurotransmitter release. Proteins involved in the SNARE complex that link P/Q-type Ca 2ϩ channels to synaptic vesicle release (SNAP-25, syntaxin, synaptotagmin) 82 play an essential role in neurotransmitter release.…”
Section: Voltage-gated Calcium Channelsmentioning
confidence: 99%